Aprovechamiento de impacto reducido: convirtiendo los resultados de la investigacion en practicas de campo - Dykstra, D.P. (1998)
In the four years since the United Nations Conference on Environment and Development (UNCED) in 1992, an important shift has taken place in the attitudes towards tropical forest management. During the UNCED meeting urged a global initiative to reduce the impact of logging operations and to develop an 'International Code for Forest Exploitation Practices'. At the same time, several development agencies as well as international non-governmental organisations began promoting reduced impact logging as a strategy for sustainable management of tropical forest. If extensive adoption of reduced impact logging and other sustainable forest management techniques does not result, confrontations with environmental groups will occur, as before. As a contribution to the debate on tropical forest sustainable management, the Food and Agriculture Organization of the United Nations (FAO) recently published the Code for Forest Exploitation Practices. The Code, designed as a general reference to be used in FAO member countries, will require some modification to adapt some of the proposed specific practices to variability of local conditions existing in the tropics. The function of a publication like the FAO Code will be to outline the general criteria for environmentally sound forest exploitation and to promote exploitation practices in accordance with these criteria.